MAL Is a Regulator of the Recruitment of Myelin Protein PLP to Membrane Microdomains. - Marjolein Bijlard; Jenny C de Jonge; Bert Klunder; Anita Nomden; Dick Hoekstra; Wia Baron (PLoS ONE, 2016)
In oligodendrocytes (OLGs), an indirect, transcytotic pathway is mediating transport of de novo synthesized PLP, a major myelin specific protein, from the apical-like plasma membrane to the specialized basolateral-like myelin membrane to prevent its premature compaction. MAL is a well-known regulator of polarized trafficking in epithelial cells, and given its presence in OLGs it was therefore of interest to investigate whether MAL played a similar role in PLP transport in OLGs, taking into account its timely expression in these cells. Our data revealed that premature expression of mCherry-MAL in oligodendrocyte progenitor cells interfered with terminal OLG differentiation, although myelin membrane formation per se was not impaired. In fact, also PLP transport to myelin membranes via the cell body plasma membrane was unaffected. However, the typical shift of PLP from TX-100-insoluble membrane domains to CHAPS-resistant, but TX-100-soluble membrane domains, seen in the absence of MAL expression, is substantially reduced upon expression of the MAL protein. Interestingly, not only in vitro, but also in developing brain a strongly diminished shift from TX-100 resistant to TX-100 soluble domains was observed. Consistently, the MAL-expression mediated annihilation of the typical membrane microdomain shift of PLP is also reflected by a loss of the characteristic surface expression profile of conformation-sensitive anti-PLP antibodies. Hence, these findings suggest that MAL is not involved in vesicular PLP trafficking to either the plasma membrane and/or the myelin membrane as such. Rather, we propose that MAL may regulate PLP's distribution into distinct membrane microdomains that allow for lateral diffusion of PLP, directly from the plasma membrane to the myelin membrane once the myelin sheath has been assembled.